Chelated zinc leaf application on nutrients concentration and yield of Mombasa grass - Teixeira, Natália Martins [UNESP]; Heinrichs, Reges [UNESP]; Bonini, Carolina Santos B. [UNESP]; Afzal, Joshua; Meirelles, Guilherme Constantino [UNESP]; Soares Filho, Cecilio Viega [UNESP]; Moreira, Adônis (Taylor & Francis, 2019)
The intensification of livestock yield requires advances in the management and fertilization of forage crops. This study was conducted to determine the dry weight yield (DWY) along with the concentration and amount of nutrients of Megathyrsus maximum cv. Mombasa. The treatments were arranged in a factorial scheme 6 × 2, six leaf rates of Zn chelate and two soil types (Entisols and Ultisol) with low and medium Zn content and four replicates. Entisols with low Zn content and Ultisol with average Zn content were used plus a control treatment with Zn sulfate. The Zn chelate and Zn sulfate foliar application did not affect the DWY. The tillering and DWY were higher in Ultisol than in Entisol. The Zn content in DWY was directly proportional to rate chelated Zn. The root dry weight yield of Mombasa grass reduced with the chelated Zn foliar application in Entisol and had no effect on Ultisol.
Keywords: forage; nutritional status; Pasture; zinc fertilization